Participação das mulheres na política autárquica em Portugal nos últimos 25 anos (1982 a 2005): especial relevo para as mulheres eleitas apuradas para a presidência dos órgãos - Nunes, Pedro (2008)
The debate around the women`s participation in politics continues to be a very present subject. This article has the intention to select, in quantitative terms, that kind of participation, particularly in the case of the autarchic local administration in Portugal, through the last 25 years. It does not intend, thus, to study the best or worse feminine performance in the respective elections and/or the exercise of the mandate. The analysis involves the 308 local governments and the 4.261 parish’s existing in Portugal. It covers almost the totality of the elected officers in the period analysed which covers the elections of 1982, 1989, 1993, 1997, 2001 and 2005,with a total of 276.068 elected men and women, where a total of 24.905 were women.